(untitled) (The Review of Diabetic Studies, 2024)
The nursing profession is an essential element of the healthcare system, with nurses playing a pivotal role in delivering quality patient care. The elevated rate of nursing job attrition has emerged as a significant problem for healthcare providers globally. The nursing shortage has emerged as a global concern, with the elevated rate of nursing job attrition greatly exacerbating this issue. Consequently, it is imperative to examine the determinants of nursing job attrition and formulate methods to mitigate it. Prior research has identified multiple factors contributing to nurse job attrition, including workload, work environment, and job satisfaction. Nonetheless, there is insufficient data regarding the specific influence of workload and work environment on nursing job attrition in Saudi Arabia. Despite the considerable influence of workload and work environment on nursing job attrition, research on this subject in Saudi Arabia is insufficient. This study seeks to address the information gap by examining the influence of workload and work environment on nurse job attrition in Saudi Arabia. This study is crucial for addressing the nursing shortage in Saudi Arabia and for elucidating the factors that lead to nursing job attrition. This study aims to elucidate the precise effects of workload and work environment on nursing job attrition, thereby offering critical insights for healthcare providers to formulate strategies that mitigate nurse job turnover and enhance patient care quality.